2012
DOI: 10.1038/mt.2012.41
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane–associated Heparan Sulfate Is a Receptor for Prototype Foamy Virus in Human, Monkey, and Rodent Cells

Abstract: Foamy viruses (FVs) (spumaretroviruses) are good alternative to retroviruses as gene therapy vector. Despite four decades since the discovery of FV, its receptor molecule is still unknown. FV vector transduction of human CD34 + cells was inhibited by culture with fibronectin. Because fibronectin contains heparin-binding domain, the interactions of fibronectin with heparan sulfate (HS) on cells might be inhibitory to FV transduction. These observations led us to investigate whether HS is a receptor for FV. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 51 publications
4
51
0
Order By: Relevance
“…While the manuscript was under review, Nasimuzzaman and Persons independently published that heparan sulfate is a receptor molecule for FV entry (28). Their results are in line with our findings with regard to the important role of HS in foamy virus cell entry.…”
Section: Discussionsupporting
confidence: 90%
“…While the manuscript was under review, Nasimuzzaman and Persons independently published that heparan sulfate is a receptor molecule for FV entry (28). Their results are in line with our findings with regard to the important role of HS in foamy virus cell entry.…”
Section: Discussionsupporting
confidence: 90%
“…SFV uses heparin sulfate to attach to target cells (47,48), but the receptor for SFV is still unknown (64). Interference studies showed that one cellular receptor is used by all SFVs (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…The broad tropism of SFV suggests a ubiquitous cellular receptor (42,43). While all SFVs seem to use the same cellular receptor (44)(45)(46), only heparin sulfate has been identified as an attachment factor so far (47,48).…”
mentioning
confidence: 99%
“…Transactivation of HMGA2 by an enhancer element in a lentiviral vector may have contributed to expansion of myeloid cells in a clinical trial for b-thalassemia major. 41 Despite the broad tropism of the foamy virus receptor, 18 only a single integration in the gut of R2203 (Chr21:20,269,587; 40.3%) appears to result from an off-target transduction. It is very likely, however, that additional offtarget events would be discovered at or near the injection site (eg, vascular endothelium), which represents a general risk to intravenous injection of a replication-deficient virus.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Foamy viral vectors have exceptionally broad tissue tropism, attributable to the foamy viral envelope receptor, heparan sulfate, expressed ubiquitously on vertebrate cell surfaces. 18 This allows them to efficiently transduce human HSC The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%